2008
DOI: 10.1007/s11214-008-9394-4
|View full text |Cite
|
Sign up to set email alerts
|

Is the Sun Embedded in a Typical Interstellar Cloud?

Abstract: The physical properties and kinematics of the partially ionized interstellar material (ISM) near the Sun are typical of warm diffuse clouds in the solar vicinity. The direction of the interstellar magnetic field at the heliosphere, the polarization of light from nearby stars, and the kinematics of nearby clouds are naturally explained in terms of the S1 super-bubble shell. The interstellar radiation field at the Sun appears to be harder than the field ionizing ambient diffuse gas, which may be a consequence of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 68 publications
1
8
0
Order By: Relevance
“…In addition, Opher (2008) could show that the resulting most likely IsMF direction is also consistent with the observations by Kurth and Gurnett (2003). Frisch (2008) linked the CHISM parameters as inferred from inner heliosphere observations through detailed modeling to the wider solar neighborhood and concluded that the physical parameters are those of a warm cloud where the Sun is located close to an interface between clouds. In addition, she made the point that the currently inferred interstellar magnetic field direction is consistent with average fields obtained for the adjacent few hundred pc from Faraday rotation observations.…”
Section: Inferring the Chism From Withinsupporting
confidence: 52%
“…In addition, Opher (2008) could show that the resulting most likely IsMF direction is also consistent with the observations by Kurth and Gurnett (2003). Frisch (2008) linked the CHISM parameters as inferred from inner heliosphere observations through detailed modeling to the wider solar neighborhood and concluded that the physical parameters are those of a warm cloud where the Sun is located close to an interface between clouds. In addition, she made the point that the currently inferred interstellar magnetic field direction is consistent with average fields obtained for the adjacent few hundred pc from Faraday rotation observations.…”
Section: Inferring the Chism From Withinsupporting
confidence: 52%
“…Comparison of the widths of absorption lines of a low mass element (e.g., D) with high-mass elements (e.g., Fe and Mg) allowed to infer the gas temperature of the LIC to be T = 7500 ±1300 K and the temperatures of the other clouds to lie in the range 3900 K (Blue) to 9900 K (Mic). Frisch (2009) and Frisch, Redfield, & Slavin (2011) noted that the inferred temperatures and nonthermal broadening parameters assume a Maxwell-Boltzman distribution of velocities and mass-independent turbulence, both of which may not be valid in low density clouds. Frisch (2009) concluded that the physical properties of the CLIC clouds are typical of warm partially-ionized gas observed elsewhere in the solar neighborhood on the basis of temperature, velocity, composition, ionization, and magnetic field properties.…”
Section: Development Of Multiple Cloud Morphologiesmentioning
confidence: 99%
“…This model explains the results of the Dominion Radio Astrophysical Observatory Low-Resolution Polarization Survey (Wolleben et al 2006), and the model consists of two synchrotron-emitting shells, S1 and S2. The same model shell S1 was used by Frisch (2009) to explain the direction of the interstellar magnetic field at the heliosphere, the polarization of light from nearby stars, and the kinematics of nearby clouds. We studied the mutual placement of these shells and our ring, and found that the ring intersects with the shell S2 in the direction (l = 256 • , b = 43 • ) at the distance of 33 pc from the Sun.…”
Section: The Ring In Spacementioning
confidence: 99%